Ponesimod inhibits astrocyte‐mediated neuroinflammation and protects against cingulum demyelination via S1P1‐selective modulation. Issue 2 (5th January 2022) - Kihara, Yasuyuki; Jonnalagadda, Deepa; Zhu, Yunjiao; Ray, Manisha; Ngo, Tony; Palmer, Carter; Rivera, Richard; Chun, Jerold
Abstract: Ponesimod is a sphingosine 1‐phosphate (S1P) receptor (S1PR) modulator that was recently approved for treating relapsing forms of multiple sclerosis (MS). Three other FDA‐approved S1PR modulators for MS—fingolimod, siponimod, and ozanimod—share peripheral immunological effects via common S1P1 interactions, yet ponesimod may access distinct central nervous system (CNS) mechanisms through its selectivity for the S1P1 receptor. Here, ponesimod was examined for S1PR internalization and binding, human astrocyte signaling and single‐cell RNA‐seq (scRNA‐seq) gene expression, and in vivo using murine cuprizone‐mediated demyelination. Studies confirmed ponesimod's selectivity for S1P1 without comparable engagement to the other S1PR subtypes (S1P2, 3, 4, 5 ). Ponesimod showed pharmacological properties of acute agonism followed by chronic functional antagonism of S1P1 . A major locus of S1P1 expression in the CNS is on astrocytes, and scRNA‐seq of primary human astrocytes exposed to ponesimod identified a gene ontology relationship of reduced neuroinflammation and reduction in known astrocyte disease‐related genes including those of immediate early astrocytes that have been strongly associated with disease progression in MS animal models. Remarkably, ponesimod prevented cuprizone‐induced demyelination selectively in the cingulum, but not in the corpus callosum. These data support the CNS activities of ponesimod through S1P1, including protective, and likely selective, effects against demyelination in a major connection pathway of the brain, the limbic fibers of the cingulum, lesions of which have been associated with several neurologic impairments including MS fatigue.